Mendesain Lintasan Belajar untuk Pengajaran Pecahan Menggunakan Pendekatan PMRI dengan Konteks Papan Catur - Ramadhan, M. Hasbi; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra (SJME (Supremum Journal of Mathematics Education), 2022)
The concepts of fractions and their operations is one of the materials that elementary school students need to master it. This research aims to produce student’s learning trajectory in understanding the concept of fractions. The approach used is Pendidikan Matematika Realistik Indonesia (PMRI) Approach and the media used is a chessboard. The use of the chessboard context is the initial activity in learning and followed with several questions related to the context used. The research method used is design research with type of validation studies. The research subjects in this study were three students in fourth grade of Madrasah Ibtidaiyah (MI) Al Munawwarah Jambi City. This research produces a learning trajectory (LT) which contains a series of learning processes that assist students to understand the concept of fractions. Based on the results of the research, it was found that the learning trajectory using a chessboard context could assist students to understand the concepts of fractions well. Keywords: Learning Trajectory, Fractions, PMRI, Chessboard